An algebra problem by Sabhrant Sachan

Algebra Level 4

Find the sum of all the positive integral values of x x satisfying

( x + 4 ) 3 + ( x + 5 ) 3 = ( x + 7 ) 3 + ( x 4 ) 3 . (x+4)^3 + (x+5)^3 = (x+7)^3 + (x-4)^3 .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sabhrant Sachan
May 1, 2016

We have, ( x + 4 ) 3 + ( x + 5 ) 3 = ( x + 7 ) 3 + ( x 4 ) 3 ( x + 4 ) 3 ( x 4 ) 3 = ( x + 7 ) 3 ( x + 5 ) 3 8 ( [ x + 4 ] 2 + [ x 4 ] 2 + ( x + 4 ) ( x 4 ) ) = 2 ( [ x + 7 ] 2 + [ x + 5 ] 2 + ( x + 7 ) ( x + 5 ) ) 4 ( [ 2 x ] 2 ( x + 4 ) ( x 4 ) ) = ( x 2 + 49 + 14 x + x 2 + 10 x + 25 + x 2 + 12 x + 35 ) 4 ( 3 x 2 + 16 ) = ( 3 x 2 + 36 x + 109 ) 12 x 2 + 64 3 x 2 36 x 109 = 0 9 x 2 36 x 45 = 0 x 2 4 x 5 = 0 x = 1 , 5 Ans = 5 \text {We have, }(x+4)^3+(x+5)^3=(x+7)^3+(x-4)^3 \\ \implies (x+4)^3-(x-4)^3=(x+7)^3-(x+5)^3 \\ \implies 8([x+4]^2+[x-4]^2+(x+4)(x-4))=2([x+7]^2+[x+5]^2+(x+7)(x+5)) \\ \implies 4([2x]^2-(x+4)(x-4))=(x^2+49+14x+x^2+10x+25+x^2+12x+35)\\ \implies 4(3x^2+16)=(3x^2+36x+109) \\ \implies 12x^2+64-3x^2-36x-109=0 \\ \implies 9x^2-36x-45=0 \\ \implies x^2-4x-5=0 \\ \implies x=-1,5 \\ \implies \color{#3D99F6}{\text{Ans = 5}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...